Features and signals in precocious citation impact: A meta-research study. - John P A Ioannidis (PLoS ONE)
The current analysis aimed to evaluate the profiles of scientists who reach top citation impact in a very short time once they start publishing. Precocious citation impact was defined as rising to become a top-cited scientist within t ≤ 8 years after the first publication year. Ultra-precocious citation impact was defined similarly for t ≤ 5 years. Top-cited authors included those in the top-2% of a previously validated composite citation indicator across 174 subfields of science or in the top-100,000 authors of that composite citation indicator across all science based on Scopus. Annual data between 2017 and 2023 show a strong increase over time, with 469 precocious and 66 ultra-precocious citation impact author profiles in 2023. In-depth assessment of validated ultra-precocious scientists in 2023, showed significantly higher frequency of less developed country affiliation; clustering in 4 high-risk subfields; high self-citations for their field; being top-cited only when self-citations were included; high citations to citing papers ratio for their field; extreme publishing behavior; extreme citation orchestration metric c/h2; and high percentage of citations given to first-authored papers compared with all top-cited authors (p < 0.005 for all signals). The 17 ultra-precocious citation impact authors in the 2017-2020 top-cited lists who had retractions showed on average 4.1 of these 8 signal indicators at the time they entered the top-cited list. In conclusion, while some authors with precocious citation impact may be stellar scientists, others probably herald massive manipulative or fraudulent behaviors infiltrating the scientific literature.